Identification and monitoring of load power quality characteristics using data mining / Muhammad Firdaus Abd Rahman - Abd Rahman, Muhammad Firdaus (2007)
The paper presents data mining application in power quality data analysis. Data mining tools are suitable for assisting in such analysis of large scale power quality monitoring data. The monitoring program involved measurement of the harmonic currents and voltages from substation.